Pengaruh Profitabilitas,Likuiditas,Solvabilitas,Aktivitas dan Keputusan Investasi Terhadap Nilai Perusahaan Manufaktur yang Terdaftar Di BEI Dengan Sturktur Modal Sebagai Variabel Moderasi - sembiring, liasta br sembiring (Fakultas Ekonomi Prodi Akuntansi, 2024)
ABSTRACT The influence of profitability, liquidity, solvency, activity and investment decisions on the value of manufacturing companies listed on the IDX with capital structure as a moderation variable. This study aims to determine the Effect of Profitability, Liquidity, Solvency, Activities and Investment Decisions on the Value of Manufacturing Companies Listed on the IDX with Capital Structure as a Moderation Variable. This study used quantitative methods. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period totaling 235 companies. Based on the sampling technique with purposive sampling, a sample of 69 companies was obtained. Data collection techniques In this study using documentation from financial statements on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The results of this study show that Profitability has a significant positive effect on company value, Liquidity has a significant positive effect on company value, Solvency has a significant positive effect on company value, Activity has a significant positive effect on company value , Activity has a significant positive effect on Company value , Investment decisions have a significant positive effect on company value, Capital structure moderates the relationship of Profitability to company value, Capital Structure moderates the relationship of Liquidity to company value. Keywords : Profitability, Liquidity, Solvency, Activity, Investment Decision, Company Value, Capital Structure